2018
DOI: 10.1039/c8ra00543e
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable adsorptive removal of nitrogen-containing compounds from hydrotreated fuel by molecularly imprinted poly-2-(1H-imidazol-2-yl)-4-phenol nanofibers

Abstract: Molecularly imprinted polymer (MIP) nanofibers were prepared by the electrospinning of poly 2-(1H-imidazol-2-yl)-4-phenol (PIMH) in the presence of various nitrogen containing compounds (N-compounds). Molecularly imprinted polymer nanofibers show selectivity for various target model nitrogen-containing compounds with adsorption capacities of 11.7 AE 0.9 mg g À1 , 11.9 AE 0.8 mg g À1 and 11.3 AE 1.1 mg g À1 for quinoline, pyrimidine and carbazole, respectively. Molecular modelling based upon density functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The physicochemical properties’ change at different storage conditions reveals the instability of the algal biocrude oils. We proposed a possible aging pathway (Figure ) of biocrude oil based on this study and the literature. ,,, …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The physicochemical properties’ change at different storage conditions reveals the instability of the algal biocrude oils. We proposed a possible aging pathway (Figure ) of biocrude oil based on this study and the literature. ,,, …”
Section: Resultsmentioning
confidence: 92%
“…However, it was observed that the UO could not be dissolved in acetone completely. Biocrude oil may form gums, sludges, deposits, precipitates, sediments, asphaltenes, or their mixture in the reaction of oil components with atmospheric oxygen and between themselves during storage. , There is consensus that the oxygen compounds, phenols, and nitrogen components (especially nitrogen heterocycle) in fuel oils show the largest contribution to the instability and sediment formation. , The significant increase of nitrogen components of the UO in the air environment indicated that oxidation and polymerization with nitrogen-containing compounds may take place to form deposits. Research showed that extracting the phenols from fuel oil resulted in a more stable fuel that is less insoluble .…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the OL in the biocrude oil was caused by the aging reactions between compounds in the biocrude and oxygen in the atmosphere. The components of the oxide layer may be gum, sediment, asphaltene, or their mixture [40,41]. Researchers agree that the oxygen-containing compounds and nitrogen-containing components, especially nitrogen heterocycles in the biocrude oil, contribute most to the oil instability and sediment formation [39,41].…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…The components of the oxide layer may be gum, sediment, asphaltene, or their mixture [40,41]. Researchers agree that the oxygen-containing compounds and nitrogen-containing components, especially nitrogen heterocycles in the biocrude oil, contribute most to the oil instability and sediment formation [39,41]. Therefore, it is essential to control the increase in oxygen and nitrogen-containing compounds during biocrude oil combustion to reduce the possibility of odor and nitrogen oxide emissions.…”
Section: Gc-ms Analysismentioning
confidence: 99%